ANALISIS SIKAP ILMIAH RASA INGIN TAHU PADA PEMBELAJARAN IPAS KELAS IV SD NEGERI 01 PABLENGAN TAHUN AJARAN 2025/2026 (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the scientific curiosity of fourth-grade students in science lessons at SD Negeri 01 Pablengan and to identify the factors influencing it. This study uses a qualitative method with data collection techniques including observation, interviews, and documentation.The results indicate that students' scientific curiosity in science lessons varies. Some students demonstrate curiosity by asking questions, participating in discussions, and seeking information related to the learning material. However, other students are less active in asking questions or participating in learning activities.Factors influencing students' scientific curiosity include teaching strategies, students' interest, and the learning environment. Therefore, appropriate learning strategies are needed to encourage students' activity and curiosity in the science learning process.